Biomimetic Tympanic Membrane Replacement Made by Melt Electrowriting. Issue 10 (27th January 2021) - von Witzleben, Max; Stoppe, Thomas; Ahlfeld, Tilman; Bernhardt, Anne; Polk, Marie‐Luise; Bornitz, Matthias; Neudert, Marcus; Gelinsky, Michael
Abstract: The tympanic membrane (TM) transfers sound waves from the air into mechanical motion for the ossicular chain. This requires a high sensitivity to small dynamic pressure changes and resistance to large quasi‐static pressure differences. The TM achieves this by providing a layered structure of about 100µm in thickness, a low flexural stiffness, and a high tensile strength. Chronically infected middle ears require reconstruction of a large area of the TM. However, current clinical treatment can cause a reduction in hearing. With the novel additive manufacturing technique of melt electrowriting (MEW), it is for the first time possible to fabricate highly organized and biodegradable membranes within the dimensions of the TM. Scaffold designs of various fiber composition are analyzed mechanically and acoustically. It can be demonstrated that by customizing fiber orientation, fiber diameter, and number of layers the desired properties of the TM can be met. An applied thin collagen layer seals the micropores of the MEW‐printed membrane while keeping the favorable mechanical and acoustical characteristics. The determined properties are beneficial for implantation, closely match those of the human TM, and support the growth of a neo‐epithelial layer. This proves the possibilities to create a biomimimetic TM replacement using MEW. Abstract : Melt electrowriting (MEW) is utilized for fabrication of biomimetic tympanic membrane (TM) replacements. These novel materials transfer the complete frequency range of the human speech while offering comparable mechanical properties to the human TM. Excellent biocompatibility is demonstrated using human keratinocytes. Coating of the MEW membranes with a sub‐µm collagen layer further improves the acoustic properties and facilitates cell adhesion.